2005
DOI: 10.1049/el:20052466
|View full text |Cite
|
Sign up to set email alerts
|

Direct quadrature phase shift keying modulator using six-port technology

Abstract: A direct quadrature phase shift keying modulator based on six-port technology is presented. The modulator comprises a six-port circuit, a switch matrix and open and short terminations. Using this modulator, direct phase shift keying modulation was achieved. Six-port technology has the advantage of signal integrity, low power consumption and physical scalability to attain different frequencies of operation and extendibility to M-ary phase shift keying. Experiment results demonstrate performance with an output p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 3 publications
0
20
0
2
Order By: Relevance
“…Considering other designs that achieve higher coverage area with full phase, our approach presents a smaller number of diodes resulting in lower power consumption and simpler control of the desired impedance value. These features are well suited for power-sensitive applications [11] and N-port-based circuits [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering other designs that achieve higher coverage area with full phase, our approach presents a smaller number of diodes resulting in lower power consumption and simpler control of the desired impedance value. These features are well suited for power-sensitive applications [11] and N-port-based circuits [6].…”
Section: Discussionmentioning
confidence: 99%
“…V ARIABLE impedances have been widely used in many problems related to communication systems, including electronically controlled attenuators [1] and modulators [2], phase shifters [3], tunable matching networks [4], adaptive radar absorbers [5], and six-port modulators [6].…”
Section: Introductionmentioning
confidence: 99%
“…The researchers then found that the six-port technique could be used for communication transceivers [2][3][4], direction finding receivers [5] and ranging receivers [6][7][8][9], etc.…”
Section: Introductionmentioning
confidence: 99%
“…It was later introduced as a direct phase modulator for a single carrier signal [4]. Previous studies showed that a direct transceiver using six-port technology has advantages such as low cost, low power consumption, simplicity and extendibility.…”
Section: Introductionmentioning
confidence: 99%
“…Each component has wideband characteristic. The operating principle of this kind of direct phase modulator has been described in previous work [4]. The essential differences while operating in UWB mode lie in the linear phase response over the wide band and uniform phase modulation at each frequency component.…”
Section: Introductionmentioning
confidence: 99%